P12.02 Glioblastoma Multiforme immunological blockades and the implications of glioma cancer stem cells. (6th September 2019) - Robilliard, L D; MacDonald, C; Angel, C E; Finlay, G J; Joseph, W; Graham, E S
Abstract: BACKGROUND: Glioblastoma Multiforme (GBM) is classified as a WHO grade IV astrocytoma that continues to circumvent classical and novel chemo-, radio- and immuno-therapies. The recent FDA approvals for the use of targeted immunotherapies against inhibitory checkpoint ligands (for melanoma; ipilimumab and nivolumab) have brought the use of monoclonal antibody therapies to the forefront of GBM research. However, poor immunological responses, exemplified by down-regulation of anti-tumour T-cell activity, and up-regulation of immunosuppressive cells and secreted factors within the tumour micro-environment, have limited the effectiveness of immunotherapy in GBM to date. Therefore, understanding how GBM modulates an extensive repertoire of immune checkpoint ligands and the functional consequence on immune evasion is necessary to develop more targeted immuno-therapeutics. MATERIAL AND METHODS: Patient derived glioblastoma cell lines were cultured using established serum-based or glioma cancer stem cell (gCSC) conditions. The phenotypes of resultant GBM cells and gCSC's were characterised using flow cytometry and immunocytochemistry, to assess expression of neural lineage and stem cell-associated markers. Thereafter, cells were screened for the expression of an extensive range of inhibitory checkpoint ligands by flow cytometry. Finally, the secretion of immune modulating factors by GBM cells and gCSC's were evaluated by using XL cytokine proteome arrays. Cytokines that appeared to be differentially expressed were subsequently measured using Cytometric Bead Arrays. RESULTS: Adherent gCSC's and gCSC derived glioma-spheres express nestin, CD44, A2B5 and vimentin, consistent with a stem cell phenotype. Furthermore, the gCSC's exhibited reduced expression of the neural lineage markers NeuN and OSP. Flow cytometry analyses revealed that glioblastoma cells expressed all 11 checkpoint ligands investigated. Interestingly, gCSC's showed higher levels of PD-L1, B7-H3, CD155 and HVEM expression than GBM cells. CONCLUSION: Glioblastoma Multiforme is highly immuno-suppressive, which is reinforced by this study. Glioblastoma cells express all the inhibitory checkpoint ligands investigated and glioma cancer stem cell cultures up-regulate expression levels further. This implies that GBM cells are heavily equipped to inhibit infiltrating T-cells, exemplifying the need to find suitable therapeutics that target multiple immuno-suppressive mechanisms simultaneously.